Treatment Factors Associated With Overall Survival in Retroperitoneal Sarcoma: An Institutional Review. Issue 10 (30th October 2020) - Kwong, Mei L.; Lee, Becky; Kunihira, Karissa; Sutjiadi, Brian; Reeves, Mark E.; Selleck, Matthew; Yang, Gary; Solomon, Naveenraj
Introduction: Retroperitoneal sarcoma (RPS) is a rare malignancy, and curative resection is considered the main therapy. Use of chemotherapy and/or radiation in addition to surgery (multimodality therapy) is controversial. Objective: To determine treatment factors that influence overall survival in RPS. Methods: This retrospective Institutional Review Board-approved study identified patients with RPS treated at a single institution between 2000 and 2017. Patient, tumor, and treatment modalities were collected. Prism (v.8.2.1) was used to calculate Kaplan-Meier survival curves. Results: There were 695 patients with sarcoma between 2000 and 2017, and 61 adults had RPS. The mean age was 59 (range 31-86) years, with 57.4% females (n = 35). Patients were 68.9% Caucasian (n = 42), 21.3% Hispanic (n = 13), 8.2% black (n = 5), and 1.6% Asian (n = 1). There were 4 patients who had neoadjuvant therapy (chemotherapy, n = 3; radiation, n = 2) and 17 who had adjuvant therapy (chemotherapy, n = 6; radiation, n = 14). There was no significant difference in survival between the groups who received multimodality therapy compared to surgery alone. There was a significant improvement in the median overall survival for patients who underwent one or multiple surgeries ( P < .05). Conclusions: These institutional data suggest that treatment factors associated with overall survival included multiple resections. Use of multimodality therapy was low and did not influence overall survival in patients with RPS compared to surgery alone.